2011
DOI: 10.7589/0090-3558-47.2.433
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Velogenic Newcastle Disease Viruses Isolated From Dead Wild Birds in Serbia During 2007

Abstract: Avian paramyxoviruses type 1 or Newcastle disease viruses (NDV) are frequently recovered from wild birds and such isolates are most frequently of low virulence. Velogenic NDV are usually recovered from poultry and only occasionally from wild birds. Five NDV isolates were obtained from carcasses of four wild bird species during 2007 in Serbia: Mallard (Anas platyrhynchos), Eurasian Sparrowhawk (Accipiter nisus), feral Rock Pigeon (Columba livia), and Eurasian Collared Dove (Streptopelia decaocto). All the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…The detection of vaccine strains in nonvaccinated flocks suggested that lentogenic vaccine strains can spread at least within poultry (30). In addition, wild-type virus transmission between wild and domestic birds was already suspected to be at the origin of the similarity of strains found in wild birds and domestic birds in live-bird markets (22,31) or in flocks with possible contacts with wild birds (7), and of the spill-back of virulent strains into wild birds (29,32). Therefore, it seems reasonable to expect that vaccine strains may also be exchanged between poultry and wild birds.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of vaccine strains in nonvaccinated flocks suggested that lentogenic vaccine strains can spread at least within poultry (30). In addition, wild-type virus transmission between wild and domestic birds was already suspected to be at the origin of the similarity of strains found in wild birds and domestic birds in live-bird markets (22,31) or in flocks with possible contacts with wild birds (7), and of the spill-back of virulent strains into wild birds (29,32). Therefore, it seems reasonable to expect that vaccine strains may also be exchanged between poultry and wild birds.…”
Section: Discussionmentioning
confidence: 99%
“…Newcastle disease (ND) is a highly contagious and infectious disease that affects almost all avian species including poultry, cage and wild life bird species [1]- [3]. It is widespread affecting many continents of the world namely; Asia, Africa, and America [4] and causes considerable economic losses, not only due to high flock mortality but also through the economic impact that may arise from trade restrictions and embargoes [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among those 23 NDV sequences representatives were also two previously isolated strains from this region (former Yugoslavia), namely YU(Vo)-1-94 and HR-Zelina-94 as representatives of NDV genotype V, as well as five strains of NDV previously isolated from wild birds in Serbia during 2007, (Vidanovi} et al, 2011). In addition to the F gene 374 nucleotides long sequences of NDV isolates obtained from poultry in Serbia, a corresponding nucleotide sequence of 23 NDV representatives of all NDV class II genotypes I -IX and genotype VII subtypes was included in the comparative analysis.…”
Section: Resultsmentioning
confidence: 97%